Performance and bacterial community structure of a submerged biofilter subjected to high ammonium and high organic carbon concentrations. (November 2016) - Rodriguez-Sanchez, Alejandro; Mikola, Anna; Muñoz-Palazon, Barbara; Vahala, Riku; Gonzalez-Martinez, Alejandro
Abstract: A partial-nitritation biofilter was tested in order to investigate the effect of organic matter loading over its performance and bacterial community structure. Analyses were done after each of a two-step organic loading of 45 days each. Without organic matter addition, the partial-nitritation biofilter performed in nearly ideal conditions in terms of ammonium oxidation to nitrite. Under these conditions its bacterial community structure was dominated by Nitrosomonas bacteria. The first loading of organic matter caused a decrease in ammonium oxidation as well as decrease in relative abundance of Nitrosomonas . The COD and BOD5 removal increased with the operation time up to 85% and 81%. For the second loading of organic matter the partial-nitritation biofilter achieved 91% and 97% in COD and BOD5 removal at the end of the experimental period but ammonium oxidation efficiency was still inefficient. The changes in the bacterial community structure of the biofilter were more pronounced at the first organic loading step as suggested by α- and β-diversity analyses. In this way, the partial-nitritation biofilter could not achieve the desired coupled ammonium oxidation and organic matter removal efficiency. Highlights: The performance of a partial-nitritation biofilter was affected by organic matter loading. Removal of COD and BOD5 was good but ammonium oxidation efficiency was poor. A net nitrogen elimination occurred via heterotrophic nitrite denitrification. Organic matter caused bacterial shift from Nitrosomonas to putative heterotrophs. Performance of the system was modeled with influent organic matter data.